Drug-related problems in hospitalized patients with type 2 diabetes mellitus: A systematic review - Jihadi, Mohammad Hisyamuddin Awang; Yuda, Ana; Sukorini, Anila Impian; Hermansyah, Andi; Shafqat, Naeem; Tan, Ching Siang; Long, Chiau Ming * (Elsevier, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is one of the non-communicable diseases which continues to rise in prevalence and mortality rate throughout the years. Drug-related problems (DRPs) are more prevalent among T2DM patients especially those with co-morbidities.